The Pretender. The complete first season [videorecording (DVD)] - Van Sickle, Craig W.; Mitchell, Steven Long; Keller, Fred. (Frederick King); Weiss, Michael T.; Parker, Andrea, 1970- (Twentieth Century Fox Home Entertainment, 2005)
Jarod is a Pretender, a genius whose exceptional intelligence allows him to assume various identities at will. He was taken from his parents at an early age and brought up in a think tank, where he believed his mind was being used to benefit mankind. When he learned that the simulations he solved were being sold to the highest bidder, he escaped. Now on the run, he searches for his true identity and tries to balance any wrong his simulations have caused.